2020
DOI: 10.1108/ijchm-04-2020-0354
|View full text |Cite
|
Sign up to set email alerts
|

How could future professionals excel in wine tourism delivery? Evidence from wine regions in emerging economies

Abstract: Purpose The purpose of this paper is to investigate the different traits, characteristics and skills future professionals need to contemplate to address the demands of the competitive wine industry, more specifically, concerning the provision of wine tourism experiences. The insights within self-determination theory are considered to develop more robust understanding of this central theme. Design/methodology/approach The views of 32 winery representatives in ownership and management roles, operating in two e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…[33], the winery experience is fundamental, as the winery works as a key element in the distribution channel and is an important element in the value chain of wine products. Therefore, it is necessary to provide training and knowledge to employees in the wine industry to improve human capital and its performance [52].…”
Section: Discussionmentioning
confidence: 99%
“…[33], the winery experience is fundamental, as the winery works as a key element in the distribution channel and is an important element in the value chain of wine products. Therefore, it is necessary to provide training and knowledge to employees in the wine industry to improve human capital and its performance [52].…”
Section: Discussionmentioning
confidence: 99%
“…Restaurant on-premise wine consumption has appeared to plateau amid coronavirus disease (COVID-19) pandemic (The Nielsen Company, 2020), but according to forecasts volume is expected to rise again in 2023, especially in some sub-categories where both on-premise sales growth and off-premise sales growth have been overwhelming during the past years. Whilst wine tourism continues to draw the attention of academics (Duarte Alonso and Kok, 2020) and the restaurant industry is expected to remain principal tourist attraction (Namkung and Jang, 2008; Pezenka and Weismayer, 2020; Li et al ., 2019), bring-your-own-bottle (BYOB) of wine restaurants are vastly emerging in many countries (e.g. USA, Australia and UK) as BYOB phenomenon is particularly linked to wine consumption (Varley, 2004; Bruwer and Rawbone-Viljoen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…CD human resources have been neglected in the literature, with only a few studies establishing the casual nature of employment (Williams, 2013), owner/manager opinion of characteristics and traits required in CD staff (Alonso and Kok, 2020) and the importance of a motivated and connected team (Crick et al , 2022). A recent wine tourism study found agreement across senior management that staff training was costly, not standardised and incumbent on individual wineries (d’Ament et al , 2021).…”
Section: Introductionmentioning
confidence: 99%